Psychological training of a lawyer as the basis of professional practical activity - Hrubinko, Andrii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The article presents the results of the study of actual features of the psychological training of a lawyer as the basis of professional legal practice. The main practical personal psychological skills that a lawyer can develop and should use in the process of professional practical activity are considered. A perspective on the use of psychological knowledge in the educational process of a higher school for lawyers is offered. The conclusions state that the modern complex conditions of social development in our country make the profession of a lawyer particularly in demand. Since it is closely integrated into society, psychological preparation, understanding of laws, approaches, techniques and methods of psychology as a science and practice comes first in practical legal activity, in addition to acquired professional knowledge during training. A new quality of legal specialist training is not possible without taking into account and applying ideas, methods, practical approaches and analysis of situations inherent in the science of psychology. Knowledge of the psychology of a lawyer and other subjects of legal relations should become thorough in the system of training lawyers in higher education, which is increasingly becoming practically oriented.